MEANING-MAKING OF INTERNET MEMES TO CREATE HUMOROUS SENSE: FUNCTIONS AS SPEECH ACTS - Fatma Rahayu Nita; Slamet Setiawan; Lies Amin Lestari (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2021)
This research explored how the memes were created with multimodal elements that could make meaning to create a humorous sense and function as speech acts. With the complexity of meaning-making, nowadays, it had become a trend that people could communicate online through Memes. Semiotics provides how the combination of modes, media, and potential meanings, that were applied to make meaning in memes. At the same time, pragmatics proposes details on how memes can function as speech acts. This research adopted a qualitative method using multimodal analysis by Leeuwen (2005) and speech acts theory by Bach and Harnish (1980) that were employed as the theoretical framework. A total of 16 memes were retrieved and captured as JPG files from social media and other internet websites; therefore, documentation was the only technique used in this research. The results of the study showed that (1) the integration of semiotic resources such as mode, media, and meaning potentials in memes aided the readers to understand the background knowledge of memes (2) two types of communicative illocutionary acts were found in the memes: constative and directive illocutionary acts which function to express the emotion or opinions and question something (3) the effects of using internet memes could be seen through verbal and non-verbal perlocutionary acts which showed an agreement and had the same feeling as in the memes. Finally, the memes containing multimodal components composed of semiotic resources interacted creatively to make humorous sense, and it could aid the readers to communicate online.